A Theoretical Exploration of Paraletrix Calculus as an Extension of Rhotrix Mathematics - Isa Yahaya; Salisu Lukunti; Umar Mujahid Aliyu; Imafidor Hassan Ibrahim; Mohammed Abubakar Kolo; Sulaiman Ahmad; Nura Hashim; Mohammed Yusuf Marafa (International Journal of Education, Management, and Technology, 2026)
Building on earlier developments in generalized matrix theory, this paper advances the mathematical framework of paraletrix calculus as an extension of rhotrix mathematics. Previous studies introduced matrix-tertions, matrix-ngittrets, and thotrices as intermediary structures between conventional vector and matrix forms, while subsequent work in rhotrix theory established several multiplication techniques and related results. Recognizing the need for a more flexible structure capable of accommodating unequal numbers of rows and columns, this study focuses on the paraletrix as a generalization of the thotrix. The paper aims to extend this framework by introducing the concepts of differentiation and integration within paraletrix calculus and by defining these operations with respect to an independent variable in functional form. Through this theoretical exploration, the study contributes to the further development of generalized matrix theory by broadening the analytical scope of paraletrix structures and opening new possibilities for formal mathematical operations within this extended system.